Investigating the effect of simulated Ischemia on phosphatases : comparing a cardiomyocytes (H9c2) cell line with a breast cancer (MDA-MB 231) cell line - Maumela, Lutendo (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.